Smartbox Sebagai Media Pembelajaran Bagi Siswa MTs di Galeri Kreatif Bantur - Astuti, Endang Setiyo; Lestari, Hernina Dewi; Nurlaila, Siti; Kurniawati, Yuni (Apik Cahaya Ilmu, 2024)
The potential-Based Community Service Program (PMBP) aims to help develop human resources in the community, accompany children to learn and develop their respective talents and interests in midwifery. This service will start from March to May 2024. The target of the learning media creation activity is Madrasah Tsanawiyah students, The method used is learning by using learning media to deliver material about basic English vocabulary and the sport of football. From these activities it can be concluded that children will be more interested in exploring learning material with fun techniques, apart from eliminating children’s boredom when learning, learning media also provides many benefits for children and makes classes more interactive and fun, with media. learners, classes become more flexible and can be done anywhere and at any time.